Lessons from Animal Models of Arterial Aneurysm - Gertz, S. David; Mintz, Yoav; Beeri, Ronen; Rubinstein, Chen; Gilon, Dan; Gavish, Leah; Berlatzky, Yacov; Appelbaum, Liat; Gavish, Lilach (AORTA, 2013)
We review the results from the most common animal models of arterial aneurysm, including recent findings from our novel, laparoscopy-based pig model of abdominal aortic aneurysm, that contribute important insights into early pathogenesis. We emphasize the relevance of these findings for evaluation of treatment protocols and novel device prototypes for mechanism-based prevention of progression and rupture.
Keywords: Abdominal aortic aneurysm; Arterial aneurysm; Animal models; Periarterial calcium chloride